Intraoperative hemidiaphragm electrical stimulation reduces oxidative stress and upregulates autophagy in surgery patients undergoing mechanical ventilation: exploratory study. Issue 1 (December 2016) - Mankowski, Robert; Ahmed, Shakeel; Beaver, Thomas; Dirain, Marvin; Han, Chul; Hess, Phillip; Martin, Tomas; Smith, Barbara; Someya, Shinichi; Leeuwenburgh, Christiaan; Martin, A.
Abstract Background Mechanical ventilation (MV) during a cardio-thoracic surgery contributes to diaphragm muscle dysfunction that impairs weaning and can lead to the ventilator- induced diaphragm dysfunction. Especially, it is critical in older adults who have lower muscle reparative capacity following MV. Reports have shown that the intraoperative intermittent hemidiaphragm electrical stimulation can maintain and/or improve post-surgery diaphragm function. In particular, from a molecular point of view, intermittent electrical stimulation (ES) may reduce oxidative stress and increase regulatory autophagy levels, and therefore improve diaphragm function in animal studies. We have recently shown in humans that intraoperative ES attenuates mitochondrial dysfunction and force decline in single diaphragm muscle fibers. The aim of this study was to investigate an effect of ES on oxidative stress, antioxidant status and autophagy biomarker levels in the human diaphragm during surgery. Methods One phrenic nerve was simulated with an external cardiac pacer in operated older subjects (62.4 ± 12.9 years) (n = 8) during the surgery. The patients received 30 pulses per min every 30 min. The muscle biopsy was collected from both hemidiaphragms and frozen for further analyses. 4-hydroxynonenal (4-HNE), an oxidative stress marker, and autophagy marker levels (Beclin-1 and the ratio of microtubule-associated protein light chain 3, I and II-LC3 II/I) protein concentrations were detected by the Western Blot technique. Antioxidant enzymatic activity copper-zinc (CuZnSOD) and manganese (MnSOD) superoxide dismutase were analyzed. Results Levels of lipid peroxidation (4-HNE) were significantly lower in the stimulated side (p < 0.05). The antioxidant enzyme activities (CuZnSOD and MnSOD) in the stimulated side of the diaphragm were not different than in the unstimulated side (p > 0.05). Additionally, the protein concentrations of Beclin-1 and the LC3 II/I ratio were higher in the stimulated side (p < 0.05). Conclusion These results suggest that the intraoperative electrical stimulation decreases oxidative stress levels and upregulates autophagy levels in the stimulated hemidiaphragm. These results may contribute future studies and clinical applications on reducing post-operative diaphragm dysfunction.